Observations of denitrification and dehydration in the winter polar stratospheres - Fahey, D. W.; Kelly, K. K.; Kawa, S. R.; Tuck, A. F.; Loewenstein, M. (1990)
It is argued that denitrification of the Arctic stratosphere can be explained by the selective growth and sedimentation of aerosol particles rich in nitric acid. Because reactive nitrogen species moderate the destruction of ozone by chlorine-catalyzed reactions by sequestering chlorine in reservoir species such as ClONO2, the possibility of the removal of reactive nitrogen without dehydration should be allowed for in attempts to model ozone depletion in the Arctic. Indeed, denitrification along with elevated concentrations of reactive chlorine observed in 1989 indicate that the Arctic was chemically primed for ozone destruction without an extended period of temperatures below the frost point, as is characteristic of the Antarctic.